Legal Accountability for Police Members who Allegedly Extorted the Suspect in a Murder Case (Case Study at the South Jakarta Metro Police) - Hans Widyatomo; Gunawan Nachrawi; Jamiatur Robekha (SEAN Institute, 2025)
One of the forms of crime that often occurs in people's lives today is the crime of extortion which is described in Articles 368 Paragraph 1 to 371 of the Criminal Code. Anyone who violates the provisions as described in Article 368 Paragraph 1 can be sentenced to a maximum of nine years in prison. extortion case carried out by 4 members of the South Jakarta Police Force. Four members of the South Jakarta Metro Police are suspected of violating the code of ethics in the form of abuse of authority in handling a case of murder and sexual exploitation of children that was revealed in April 2024. Even in this case, it is strongly suspected that it involves other parties. Victims of extortion as well as suspects of murder and child sexual violence feel harmed up to billions of rupiah. The formulation of the problem discussed is: 1) What is the qualification of a criminal act that can be categorized as extortion according to Indonesian criminal law? and 2) What is the legal accountability for police members who are suspected of committing the crime of extortion?. The research method used is the normative juridical method, namely research that prioritizes literature data, namely research on secondary data. The secondary data can be in the form of primary, secondary or tertiary legal materials. Based on the results of the research, the author concludes that legal accountability for police members who are suspected of committing the crime of extortion is by effectively enforcing the law against police officers who commit extortion with the importance of implementing a strict and transparent criminal legal process. As seen in the case of a member of the South Jakarta Police who had extorted the suspect in the murder case. As law enforcement officers, the police must be subject to the same rule of law as the general public, as stipulated in Article 29 of the Police Law.